Manipulation of the mare’s estrous cycle using follicular ablation and effects of maternal dietary omega-3 supplementation on reproductive traits and markers of foal bone metabolism - Buist, Sterling Elizabeth (Kansas State University, 2019)
Two experiments were conducted to determine the practicality of utilizing follicular ablation (FA) in mares. Experiment 1 investigated the efficacy of FA as a technique for ovulation synchronization. Twenty non-pregnant mares were assigned to the ablation (FA) or P+E (progesterone + estradiol) treatment (n = 10/treatment). In the FA treatment, follicles > 10 mm were ablated (d 1) and mares were administered PGF[subscript 2α] on d 5. Mares received hCG d 11 and ovaries were monitored via transrectal ultrasound until ovulation. The P+E mares received 150 mg P + 10 mg E for 10 d with concurrent PGF[subscript 2α] administration d 10. Ultrasound monitoring began on d 15 continuing until ovulation. On d 18, P+E mares received hCG. Interval from initiation of treatments to ovulation and interval from hCG administration to ovulation was reduced (P < 0.01) in response to FA. Ablation may be an acceptable, non-steroidal alternative for synchronization of ovulation and has the ability to shorten the interval from treatment to ovulation. The objective of Experiment 2 was to determine if FA could prolong the postpartum interval to ovulation. Eighteen postpartum mares were assigned to receive FA (n = 10) or be untreated controls (CON, n = 8). In FA mares, follicles > 10 mm were ablated on d 6 postpartum. Mares were administered PGF[subscript 2α] on d 11 and monitored via transrectal ultrasound until ovulation. When a follicle ≥ 35 mm was detected, mares received hCG. The CON mares were evaluated via ultrasound beginning on d 4 postpartum until a follicle ≥ 35 mm was detected. Mares were then administered hCG and ovaries were monitored until ovulation. Compared with controls, ablation prolonged (P < 0.01) the interval from foaling to ovulation and could be utilized to optimize the timing of breeding to improve postpartum conception rates. Existing research is limited on foal bone development in response to peri-partum maternal supplementation of n-3 fatty acids. Experiment 3 investigated the effect of maternal n-3 fatty acid supplementation on neonatal bone metabolism and mare reproductive traits. Seventeen pregnant stock-type mares were assigned to either of two treatment diets: Control (CON; n = 8, concentrate with no fat supplementation) or fat-supplemented (FS; n = 9, concentrate plus Gromega™, which provided 13.475 g of eicosapentaenoic acid (EPA) and 11.162 g of docosahexaenoic acid (DHA) per day). Treatment began 8 wk before expected foaling date. Blood samples were collected every other week throughout the trial and additional sampling occurred once a follicle > 30 mm was first detected post-foaling and continued until d 5 post-ovulation. Serum was analyzed for progesterone (P4) and insulin-like growth factor-1 (IGF-1). Follicular activity was monitored via transrectal ultrasound from d 4 postpartum until ovulation. Foal blood collection occurred weekly for 8 wk. At 2 and 4 wk of age, synovial fluid (SF) was collected and submitted for cytology. Plasma and SF were evaluated for markers of bone metabolism. Plasma DHA and EPA were increased (P < 0.05) in the FS mares and their foals. No differences (P > 0.05) were detected in gestation length, concentrations of IGF-1 or P4, or the postpartum interval to ovulation. In addition, no differences were detected in foal plasma metabolites, SF prostaglandin E2, or osteocalcin. Compared with CON, SF carboxy-terminal cross-linked telopeptide of type 1 collagen (ICTP) was greater (P < 0.05) in the FS treatment at wk 4 and SF total protein was greater (P < 0.05) at both time points in the FS treatment. A correlation was detected (P < 0.05) between synovial and plasma ICTP concentrations (r = 0.49). Maternal n-3 supplementation did not affect mare reproductive traits and had a minimal effect on foal bone metabolism in healthy foals fed to meet their requirements.
Keywords: Mare; Follicular ablation; Omega-3; Synchronization; Bone